Discipline and Indulgence : College Football, Media, and the American Way of Life during the Cold War - Montez de Oca, Jeffrey (Book collections on Project MUSE., 2013)
The early Cold War (1947-1964) was a time of optimism in America. Flush with confidence by the Second World War, many heralded the American Century and saw postwar affluence as proof that capitalism would solve want and poverty. Yet this period also filled people with anxiety. Beyond the specter of nuclear annihilation, the consumerism and affluence of capitalism's success were seen as turning the sons of pioneers into couch potatoes. In Discipline and Indulgence, Jeffrey Montez de Oca demonstrates how popular culture, especially college football, addressed capitalism's constradictions by integrating men into the economy of the Cold War as workers, warriors, and consumers. In the dawning television age, college football provided a ritual and spectacle of the American way of life that anyone could participate in from the comfort of his home. College football formed an ethical space of patriotic pageantry where men could produce themselves as citizens of the Cold War state. Based on a theoretically sophisticated analysis of Cold War media, Discipline and Indulgence assesses the period's institutional linkage of sport, higher education, media, and militarism and finds the connections of contemporary sport media to today's War on Terror. -- from back cover.